UNVEILING THE SHADOWS: ANALYSING SOCIAL STIGMA IN GILLIAN FLYNN'S DARK PLACES (International Journal of Food and Nutritional Sciences, 2022)
Social stigma remains a pervasive force in society, manifesting in discrimination based on various factors such as culture, gender, race, socioeconomic class, and health. This paper delves into the psychological and sociological ramifications of social stigma on individuals, drawing insights from Gillian Flynn's novel "Dark Places," which vividly portrays the repercussions of social discrimination within the context of a struggling family in Kansas City. The paper begins by defining social stigma as the systematic devaluation and discrimination against individuals or groups based on perceived differences. It explores how victims of stigmatization often experience a negative transformation in their identity, leading to a sense of alienation and a "spoiled" identity. Additionally, it examines the phenomenon of identity threat, wherein stigmatized individuals may attempt to align themselves with the discriminating group as a coping mechanism. A critical aspect of social stigma is its transmission across generations and its capacity to permeate societal norms and beliefs. Recognizing the various forms of stigma is essential for dismantling its pervasive influence on individuals and communities. Drawing from Flynn's narrative, the paper highlights how economic hardships and social discrimination contribute to the unraveling of familial bonds and individual psyches. Through a research-oriented lens, this paper aims to analyze the psychological and sociological dimensions of social stigma, emphasizing its profound impact on individual well-being and societal dynamics. By examining real-world implications through the lens of literature, it seeks to contribute to a deeper understanding of the complex interplay between stigma, identity, and societal structures.